Analisis Kesulitan Siswa Dalam Pembelajaran Jaringan Komputer Di SMK Budi Luhur - frida_anjelia_dyah hari irawan (JURNAL KEILMUAN TEKNOLOGI DAN PENDIDIKAN TERPADU, 2025)
This study aims to analyze students’ learning difficulties in computer network subjects at SMK Budi Luhur, which may affect their academic achievement and readiness to enter the workforce. The research employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The subjects of this study were students from grades X, XI, and XII in the Computer and Network Engineering program. The findings reveal that students’ learning difficulties include unbalanced learning outcomes, delays in completing assignments, inappropriate attitudes during lessons, and deviant behaviors. The causes of these difficulties consist of internal factors, such as low motivation, interest, and concentration, as well as external factors, such as limited school facilities and less varied teaching methods. The scope of this study is limited to a single school and one subject, computer networks; therefore, the results cannot be broadly generalized. The practical implications of this research provide valuable input for schools and teachers to improve instructional strategies, for instance by adopting more interactive methods and providing adequate learning facilities. From a social perspective, this study highlights the importance of support from both the school environment and families in overcoming students’ learning difficulties. The originality of this research lies in its specific focus on analyzing learning difficulties in computer network learning at vocational schools, a topic that has rarely been explored in depth.